Food waste awareness among hospitality students in Universiti Malaysia Kelantan - Nik Nurzahira Natasha Fauzi; Nur Athirah Tompang; Raja Maizatul Akma Raja Ahmad; Suhaili Shahirah Abdul Basib (2021)
Food waste can be defined as food that is discarded from human intake, whether it is other food that has been preserved or left a reputation after being eaten. This food waste has also affected large environments such as odour pollution, air pollution and soil pollution that go through the process of transformation and decomposition. In addition, this food waste can be reused as compost, animal feed or raw materials such as biogas generation. In addition, this wastage occurs is due to a handful of working women who often commit wastage of expired food due to busy work and not having time to cook. Indirectly the disposal of expired food waste such as vegetables and fruits can be recycled as dishwashing products or organic flooring. In addition, to being chemical -free and environmentally friendly, it also saves on student expenses. Furthermore, there is food waste that occurs among hospitality students at the Universiti Malaysia Kelantan. As a result, the researcher has made a study on food waste among such students. Therefore, this study is to find out about the awareness of food waste among Hospitality Students at Universiti Malaysia Kelantan. Thus, there are 238 respondents who have followed this study who use social media methods such as Google Form, WhatsApp, E-mail, and others. Furthermore, this study can pay attention to the awareness of food waste among hospitality students at Universiti Malaysia Kelantan. The results of this study have shown that regarding the behaviour, knowledge and level of concern for food waste in hospitality students.